Some aspects of the marketing of milk in Northern Ireland - Armstrong, D. L. (Statistical and Social Inquiry Society of Ireland, 1959)
Though the milk bottle and the milkman are familiar sights it is doubtful if the general public ever give much thought to the complex organisation which ensures the daily delivery of milk to some 338,000 households in Northern Ireland. And this is only one aspect though a very important one of the milk industry in Northern Ireland. What is the milk industry? Its basis is the production of milk on some 22,000 farms which means that one out of every 64 in the population is a milk producer (cows' milk of course!). A first call on the milk produced is the market for liquid milk for human consumption. The balance is utilised in the manufacture of dairy products in factories of varying size and complexity. In this paper I have attempted to outline the growth of the industry, to describe its present state, to show the part played by the Milk Marketing Board for Northern Ireland and to point to some of the problems which face the industry. The paper thus covers a wide field and is for this reason of a general nature. I thought, however, that a general survey would be of greater interest to the members of the Society than a more detailed examination of some particular problems.
Read before the Society, February 23 1959
Keywords: Agricultural marketing; Northern Ireland dairy industry; Northern Ireland milk industry; 314.15